That's not us [videorecording (DVD)] - Sullivan, William C. (Filmmaker); Sullivan, William C. (Filmmaker); Berger, Mark; Wharton, Sarah; Gray, Elizabeth ([Publisher not identified], 2016)
Three twenty-something couples; gay, lesbian and straight, travel to an upstate New York beach house to enjoy the last days of summer, but what was meant to be a fun, carefree retreat transforms into an intimate exploration of sex and commitment. Moment-to-moment, relationships are tested as tensions between the couples and friends begin to simmer.